Il montaggio delle espressioni. Gli album e le serie nel confronto tra repertori visivi: il caso Adelaide Ristori e Herbert Watkins - Samantha Marenzi (Drammaturgia)
The photographic collection of Adelaide Ristori Archive kept at the Museo Biblioteca dell’Attore in Genoa consists of hundreds of prints, some of which are collected in albums or series. Divided according to different criteria and mixing private and theatrical photographs, the albums collect pictures taken by photographic studios scattered all over the world. The passage of the actress, with her characters, costumes, and fragments of her repertoire, traces an international history of photography and visual culture. Her face participates in a macroscopic gallery of portraits appearing in turn in other series and albums organized according to the photographers’ strategies. This is the case of Londoner Herbert Watkins, author of a collection of well-known faces where also the Italian actress appears. By including her in his album of portraits, Watkins introduces Ristori to the scene of Victorian photography, where the faces of the subjects are overlaid with the features of the social and theatrical roles they played. The comparison of these repertoires based on the opposite criteria (one subject many photographers/one photographer many subjects) reveals the layers on which the actress’s memory is deposited. The same photographs observed in different contexts show the enduring and multifaceted effectiveness of her expressive gesture.